Influence Of Temperature On Changes In Ph Of Appreting Solutions In The Presence Of Various Catalysts - Sativaldiev Aziz Kahramanovich (Zien Journals, 2024)
The correct choice of catalyst, its concentration, nature and its activity in cross-linking reactions of cellulose molecules play a decisive role in the quality finishing of fabrics.
Keywords: finishing; finishing agent; macromolecule